Intravoxel incoherent motion diffusion-weighted MRI in patients with breast cancer: Correlation with tumor stroma characteristics. Issue 120 (November 2019) - Li, Yuan; Wang, Zhengping; Chen, Feng; Qin, Xin; Li, Changqing; Zhao, Yingman; Yan, Chenggong; Wu, Yuankui; Hao, Peng; Xu, Yikai
Highlights: Tumor stroma ratio and dominant stroma type were independent prognostic factors of solid tumors. D and f values showed significant differences according to TSR of breast cancer. The D value was lower in collagen dominant type than in fibroblast dominant or lymphocyte dominant type of breast cancer. Abstract: Purpose: To determine whether imaging parameters derived from intravoxel incoherent motion (IVIM) diffusion weighted imaging (DWI) vary according to tumor-stroma ratio(TSR) or dominant stroma type of breast cancer. Methods: We prospectively enrolled 77 patients with breast cancer who underwent IVIM DWI on a 3.0 T MR scanner. The values of IVIM parameters (D, D* and f) were measured. After surgery, TSR or dominant stroma type was evaluated. The relationship between imaging parameters and tumor stroma characteristics was analyzed. Results: The mean D and f values were lower in stroma-poor tumor than in stroma-rich tumor ( P = 0.012, 0.015). The mean D value was lower in the collagen-dominant type than in fibroblast-dominant or lymphocyte-dominant type ( P = 0.032, 0.043). According to multivariate linear regression analyses, tumor size ( P = 0.007), TSR ( P = 0.008), dominant stroma type (collagen dominant, P = 0.012), and histological grade ( P = 0.031) were independently correlated with D value; and tumor size ( P = 0.011), TSR ( P = 0.021) and histological grade ( P = 0.037) were independently correlated with f value. Conclusion: In breast cancer, D and f values show significant differences according to TSR, and D value is lower in collagen dominant type than in fibroblast dominant or lymphocyte dominant types.